Sequências com figuras geométricas na obmep: resolução e construção dos problemas - Ferreira, Evanilson Vicente (Universidade Federal Rural do Semi-Árido, 2019)
Mathematics has been changing over the years in line with the requirements imposed by man. With the advancement of Mathematics as Science, it becomes increasingly important to search for instruments that arouse students' interest. In this sense, several Mathematical Olympiads are applied worldwide to encourage and discover new talents. However, often the way students are prepared for these Olympics or even for school life does not arouse interest because the applied methodologies do not fit the technological world in which they are inserted. In this way, this work seeks to offer a tool that helps to understand the algebraic resolution of problems by means of the construction and visualization of the elements involved, putting them in motion and making the dynamic exercises using GeoGebra Software. This idea has as its focus the study of mathematical sequences formed by geometric figures inserted in the tests of the Brazilian Mathematics Olympiad of Public Schools (OBMEP), but that can be extended to the study of other Mathematical contents.
Keywords: Ensino; Aprendizagem; OBMEP; GeoGebra; Metodologia; Teaching; Learning; OBMEP; GeoGebra; Methodology; CIENCIAS EXATAS E DA TERRA::MATEMATICA